2021
DOI: 10.3168/jds.2020-19172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic Minas Frescal cheese on the volatile compound and metabolic profiles assessed by nuclear magnetic resonance spectroscopy and chemometric tools

Abstract: This study aimed to evaluate the effect of Lacticaseibacillus casei 01 as a probiotic culture on the production of volatile organic compounds and metabolic profile of Minas Frescal cheese. Lactose (α-lactose and β-lactose), fatty acids (unsaturated and saturated), citric acid, tryptophan, and benzoic acid were the main compounds. Compared with the control cheese, probiotic cheese was characterized by the highest concentration of tryptophan and presented a higher number of volatile acids. The control cheese was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The success of MRI scanning has a direct impact on the diagnosis of the disease. High quality nursing service is the key to ensure the successful and safe completion of MRI scanning and ensure the image quality [ 6 , 7 ]. Masuda, R. and others pointed out that effective nursing intervention for patients undergoing MRI Dynamic enhancement scanning can alleviate their negative emotions before the examination and maintain a peaceful state of mind during the examination, so as to help them successfully complete the examination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The success of MRI scanning has a direct impact on the diagnosis of the disease. High quality nursing service is the key to ensure the successful and safe completion of MRI scanning and ensure the image quality [ 6 , 7 ]. Masuda, R. and others pointed out that effective nursing intervention for patients undergoing MRI Dynamic enhancement scanning can alleviate their negative emotions before the examination and maintain a peaceful state of mind during the examination, so as to help them successfully complete the examination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cheese is a mass of casein and milk fat, among other components that are present in milk, with the addition of yeasts, salt, dyes, and other substances allowed under current legislation. The cheese-making process is based on three stages, namely, acidification, coagulation, and dehydration, which is the removal of whey [39,40].…”
Section: Probiotic Cheesementioning
confidence: 99%
“…S. Enteritidis ATCC 13076 and E. coli O157:H7 NCTC 12900 were susceptible to all of the lactobacilli strains. Balthazar et al (2021b) reported that, the addition of probiotic L. casei culture; decreased the lipolysis, promoted the proteolysis, and increased the volatile compounds. Davoodabadi et al (2015) previously determined that L. rhamnosus GG, L. fermentum 89-1, and L. paracasei 6-4b isolated from healthy infant feces inhibits the growth of S. Enteritidis H7.…”
Section: Antimicrobial Activitymentioning
confidence: 99%